The relationship between motor development and social adaptability in autism spectrum disorder - Chen, YanJie; Fei, Xi; Wu, TianChen; Li, HongJuan; Xiong, NiNa; Shen, RuiYun; Wang, Ying; Liang, AiMin; Wang, Huan (Frontiers in Psychiatry, 2022)
Objectives Autism spectrum disorders(ASD)describe a wide range of pervasive developmental disorders by core symptoms including deficits in social communication and interaction, as well as restricted, repetitive, and stereotyped behaviors. At the same time, some children with autism are accompanied by motor development disorder. Many studies have confirmed that the motor development impairment was significantly associated with the social problems associated with ASD. Thus, this study aimed to investigate how motor development affects social adaptability in children with ASD to provide references for early ASD intervention. Materials and methods The case data of children’s health care were selected in 2021. Motor development was assessed with the Developmental Behavior Assessment Scale for Children Aged 0–6 years. Social adaptability was measured using the Japanese S-M Social Living Skills Scale. Statistical analysis was conducted with SPSS 22.0 software package. Data were analyzed using independent samples t-test and logistic regression. Results A total of 198 cases comprising 140 boys (70.71%) and 58 girls (29.29%) were included, and the average age of participants was 3.40 ± 1.06 years, with 3.33 ± 1.18 years in the typical development (TD) children group and 3.46 ± 0.95 years in the ASD group. The social adaptability of 107 ASD children was abnormal, including 37 children (34.5%) with marginal, 48 children (44.9%) with mild, 17 children (15.9%) with moderate, and 5 children (4.7%) with severe. In 91 TD children, there were 51 children (56.04%) with normal social adaptability, 38 children (41.75%) with marginal, 2 children (2.19%) with mild, and nobody with moderate or severe. The ASD children had lower levels of developmental behavior than those of TD children, and the difference was statistically significant. The results of logistic regression showed that fine motor increased by 1 unit, and the OR value of one level decreased in social adaptability was 2.24 times (OR = e0.807 = 2.24). Conclusion In children with ASD, not only motor development is delayed, but also social adaptability is affected, and fine motor skill may be important for social adaptability.